Slade, London, Asia: Contrapuntal Histories between Imperialism and Decolonization 1945–1989 (Part 1) - Liz Bruchet; Ming Tiampo (British Art Studies, 2021)
This feature takes the Slade School of Fine Art as the starting point for a global microhistory and reimagines ways of engaging with, co-constituting, and curating a research archive in pursuit of this endeavour. It consists of two parts: contributions in this issue of British Art Studies focus on the immediate post-war period, roughly 1945 to 1965, and a forthcoming second part will consider the 1960s to the 1990s. In this issue, the feature comprises a narrative history that interrogates the Slade’s role as a contrapuntal node, and a companion archival feature that brings together materials from multiple institutional and personal archives in Asia and the United Kingdom (UK). Building upon Edward Said’s use of the musical metaphor of contrapuntalism to address both the presence of empire in the metropolis and the construction of a transnational counterpoint with multiple voices, this project seeks to surface histories at the intersection of art education, imperialism, and decolonization. By using the Slade as a transversal line that connects multiple people and histories from Bangladesh, India, Pakistan, Hong Kong, Taiwan, Indonesia, Singapore, Nigeria, Sudan, Uganda, Britain and beyond, this essay proposes new ways of writing histories of contrapuntal—not multiple—modernisms, as well as understanding art in Britain itself as a product of empire.